Spray-coated epoxy barrier films containing high aspect ratio functionalized graphene nanosheets. Issue 124 (30th November 2015) - Li, Peng; Huang, Tsao-Cheng; White, Kevin L.; Hawkins, Spencer; Kotaki, Masaya; Nishimura, Riichi; Sue, Hung-Jue
Abstract : Epoxy nanocomposite spray-coatings containing large aspect ratio modified graphene (MG) were successfully prepared in a facile manner. Abstract : Epoxy nanocomposite spray-coatings containing large aspect ratio modified graphene (MG) were successfully prepared in a facile manner. The individually exfoliated MG nanosheets form liquid crystalline mesophases in the epoxy precursor at low loadings. The epoxy/MG nanocomposite films exhibit significantly improved gas barrier properties even in humid conditions. The spray-coating method allows for the preparation of high MG content nanocomposites in large scale without compromising processability. Implication of the present finding for fabrication of high-performance graphene-based packaging films with multi-functionality is discussed.